Analyzing the impact of international trade on the growth of national economies and overcoming global economic challenges - Mustafa Ismail Khalil (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
International trade is essential since it mainly contributes to expanding countries ' markets and the availability of goods and products that may not be available locally. The research aimed to analyze the impact of international trade on the growth of national economies and overcoming global economic challenges. One of the most important results is the increase in the value of world exports between 2010 and 2022, from (19082) billion dollars to (31583) billion dollars. China, the United States, and Germany have ranked at the top of the exporting countries, and imports for the same period increased from (19227) billion dollars to (31608) billion dollars in 2022. The United States has occupied the leading position with (3376) billion dollars. The most important proposals are to develop productive sectors using modern technical and technological methods to increase production efficiency, encourage exports, and reduce imports.